2014
DOI: 10.1002/vipr.201400546
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of the CdS buffer layer in CIGS thin‐film solar cells

Abstract: This contribution provides an overview of current activities in the area of alternative buffer layers for Cu(In,Ga)(S,Se)2 (CIGS) thin‐film solar cells. Good cell and module results were achieved by replacing the standard Cds buffer with Zn(O,S), In2S3, (Zn,Sn)Oy or (Zn,Mg)O grown by various methods like chemical bath deposition (CBD), thermal evaporation, sputtering, atomic layer deposition, and spray ion layer gas reaction. The “dry” deposition methods like sputtering and thermal evaporation could be favorab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…[ 30 ] Zn-compound buffer layers exhibit wider band gaps and therefore less light absorption than CdS, which should lead to higher current densities of solar cells. Most CBD recipes for Zn-compound buffers follow a deposition route very similar to CdS as seen in [ 81 ] Copyright 2014, Wiley-VCH. thiourea as sulfur source and ammonia are mixed together, and the deposition temperature is typically 60-80 °C.…”
Section: Chemical Bath Deposition Of Cds and Zn(sooh)mentioning
confidence: 98%
See 1 more Smart Citation
“…[ 30 ] Zn-compound buffer layers exhibit wider band gaps and therefore less light absorption than CdS, which should lead to higher current densities of solar cells. Most CBD recipes for Zn-compound buffers follow a deposition route very similar to CdS as seen in [ 81 ] Copyright 2014, Wiley-VCH. thiourea as sulfur source and ammonia are mixed together, and the deposition temperature is typically 60-80 °C.…”
Section: Chemical Bath Deposition Of Cds and Zn(sooh)mentioning
confidence: 98%
“…[ 80 ] A number of review papers comprehensively describe the deposition of buffer layers by CBD, atomic layer deposition (ALD), ion-layer gas reaction (ILGAR), ultrasonic spray pyrolysis (USP), metal organic chemical vapor deposition (MOCVD), ED, sputtering and evaporation (PVD). [ 79,[81][82][83][84] The "soft" non-vacuum methods prevail because they offer a conformal and uniform deposition of thin (30-100 nm) layers on the rough absorber surface without the concern of plasmainduced damage as in the case of sputtering. In the following three sub-sections we will review three solution approaches proven to yield high-effi ciency CIGS devices.…”
Section: Buffer Layermentioning
confidence: 99%
“…This buffer layer serves as the n portion of the p-n junction and typically has a thickness of 0.05-0.1 μm [16]. CdS is a good choice for this buffer layer because it has a bandgap of 2.4 eV, which allows a majority of photons to pass through to the Cu(InGa)Se 2 absorber layer [19]. Only photons with a wavelength shorter than 500.0 nm can be absorbed by the CdS layer.…”
Section: N-cds/cu(inga)se 2 Solar Cell Designmentioning
confidence: 99%
“…ZnO has a bandgap of 2.8 eV, which increases the wavelength spectrum that passes through the buffer layer into the absorber layer [19]. Despite the promise of ZnO buffer layers, many studies demonstrated that using ZnO in place of CdS results in a cell with a 3-5% lower efficiency [16].…”
Section: Developments In Cu(inga)se 2 Designmentioning
confidence: 99%
“…These costs could be eliminated if a Cd‐free buffer material could be identified, which can be deposited by means of vacuum techniques. A promising candidate is indium sulfide (InxSy) as it can be deposited by physical vapor deposition (PVD) ().…”
Section: Introductionmentioning
confidence: 99%